Design and Parametric Optimization Of Heavy Duty Leaf Spring (International Journal of Engineering and Computer Science, 2015)
The project deals with the analysis of a leaf spring, which is employed in heavy duty vehicle belonging to the medium segment of the Indian automotive market. In the design of this kind of spring both the elastic characteristics and the fatigue strength have to be considered as significant aspects. In addition to this particular elastic property, as a consequence of the research effort in reducing the mass of components typical of the automotive industry, these springs have to face very high working stresses. The structural reliability of the spring must therefore be ensured. So for this purpose the static stress analysis using finite element method has been done in order to find out the detailed stress distribution of the spring. In this spring is analyzed for stresses and deflection and same as plotted. Nine different parameters have chosen for the analysis. In this project main aim is to improve the fatigue strength by reducing shear stress of the spring, so each material is analyzed for its displacements and stresses. The material with the lowest displacement and stress is selected. The software used for the finite element meshing is ANSYS. Result values obtained for deflection and stresses are compared for each material. This project deals stress variations for all the set of parameters, and to pick the best spring among the rest.